Digital Marketing, Influencer, Social Media, and Health: A Bibliometric and Thematic Analysis - Ifta Firdausa Nuzula; Nurhasanah; Riza Seti Roikhanah (The Indonesian Institute of Science and Technology Research, 2025)
The rapid growth of digital marketing in the health sector has redefined how individuals access, interpret, and engage with health information. Social media and influencers play a significant role in disseminating health knowledge, shaping public perceptions, and even influencing health behaviors. However, this expansion has also brought challenges related to misinformation, the reliability of health communication, and the integration of digital strategies into evidence-based healthcare. This paper presents a bibliometric analysis using VOSviewer with data from Dimensions.ai (2020–2025), identifying four major thematic clusters: (1) health literacy and psychological factors, (2) effectiveness of digital health interventions, (3) evidence-based knowledge dissemination, and (4) policy, misinformation, and healthcare services. The discussion explores the interplay between these clusters and their implications for health communication, marketing strategies, and public policy. Findings highlight the dual potential of social media and influencers in both supporting evidence-based health promotion and propagating misinformation. Recommendations include enhancing collaboration between policymakers, researchers, and digital actors to foster a reliable and sustainable digital health ecosystem.